COASTAL STUDIES FOR IMPLEMENTATION OF LAW 27/2007 IN SIDOARJO - Aries Dwi Siswanto; Widi Agoes Pratikto; Suntoyo .; Kriyo Sambodho; Siti Nurlaela (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Law 27/2007 is the very basic rules for making the composition as well as planning and management tool on the ocean / beach / small islands. Law 27/2007 assumed less informed and not recognized by the staff of the government or society in general. This paper aims to identify the extent of socialization of Law 27/2007 by the relevant stakeholders, identify what factors or variables that have been well received and well prepared to implement Law 27/2007. Coastal and marine areas are relatively large with a variety of problems into consideration in determining Sidoarjo regency as a research location. There are two factors that were assessed, namely the level of knowledge of the material or content of the Law 27/2007 and the level of readiness for the implementation of Law 27/2007. Factor is defined by a number of variables and indicators. Methods of analysis using the Multi Dimensional Scaling with ALSCAL procedure to map a number of indicators. Identify the level of knowledge and level of readiness for the implementation of Law 27/2007 on the respondents showed very weak. There are varying levels of knowledge, although the general information about the Act is informed by good, but the policies, programs and tools to implement the government or community level have not adequate yet.